Propuesta de Transferencia de la Gestión del conocimiento a través de un diseño de Inducción en la empresa HeadBand S.A.S (2020)
Every company must understand the importance of knowledge in all its fields, since this allows us to recognize that both customers and employees are a fundamental part of the business process. The transfer of knowledge for the company HeadBand SAS necessarily implies the acquisition and modification of the information from the moment it is proposed both for induction, as well as for customer service and training, thereby contributing to the reduction of low productivity, and demotivation. In order to perform better, the company HB must give priority to induction, customer service and training, in order to keep its employees and its buyers satisfied. In this way, proper training improves the efficiency and productivity of employees, reducing loss of time, money and resources.